Sensitivity analysis of a photovoltaic solar plant in Chile. (March 2016) - Bustos, F.; Toledo, A.; Contreras, J.; Fuentes, A.
Abstract: A total of 22 cities in Chile were analyzed focusing the development of a 30 MW Photovoltaic Solar Plant using RETScreen software. Results of the study indicate that Calama City presents interesting results, with a Capacity Factor of 34.0% and an Energy Production of 92523 MWh. However, with a discount rate of 12% and an evaluation of 30 years, a Net Present Value (NPV) of −67 × 10 6  USD and an Internal Rate of Return (IRR) of 7.0% were obtained due to the high investment cost. Applying a 40% incentive in Calama City, the NPV reaches 11 × 10 6  USD, with an IRR of 13.7%, thus obtaining positive financial results. Sensitivity analysis, without the incentive applied, considers the variation of ±30% for five parameters, indicating that the initial cost and the electricity export rate significantly influence the results of the project. A risk analysis was performed on these parameters indicating that an NPV ≤ 0 and an IRR ≥ 12% were reached for 94.0% and 7.0% of the projects, respectively considering the initial cost. Analyzing the electricity export rate, only 5.0% of the projects had positive results for NPV and only 4.0% of the projects meet the criteria established for the IRR. Highlights: The potential for a PV solar plant was evaluated for 22 cities in Chile. Initial cost, capacity factor, energy conversion and GHG reduction were studied. From 22 locations, only one city in northern Chile exhibited favorable results. The probability to obtain positive financial results was lower than 7%.